Incorporação da gestão dos custos do ciclo de vida ao processo de desenvolvimento do produto da EMBRAER. - Freixo, Osvaldo Magno (Universidade Federal de São Carlos, 2004)
The Product Development Process (PDP) is one of the fundamental business processes of an organization and therefore should be conducted harmonically with the other company processes, as well as with the established strategies for competitiveness and profitability. One of these strategies is to offer the market products at reduced costs, which is a result of development, manufacturing, operation, maintenance and even discarding products once they have reached the end of their life cycle. These costs, called Life Cycle Costs (LCC), are closely related to Product Development, since the decisions taken during its process define costs in each phase of the product s life cycle. A Product Development Model should include a definition of the activities, information and responsibilities regarding the impact that each engineering decision has on the product s Life Cycle Costs. This definition leads to a LCC Management Model, considered, then, a sub-model of PDP. The objectives of this research were as follows: (a) to incorporate LCC management activities into the PDP of a company, with the participation of people that work with Product Development; (b) based on the literature and the case study developed, to prepare guidelines with recommendations for companies interested in implementing a similar project. The Action-research method was used in the study, and the LCC Management Model was developed at EMBRAER Empresa Brasileira de Aeronáutica S/A (a Brazilian aeronautics company). The main conclusions of our research indicate that the involvement of the people that participate in the PDP is crucial when preparing the LCC management models. However, these people should be adequately prepared to take part in a project of this nature, enabling real management and the implementation of a company culture concerning LCC. The results have also shown that the Action-research method is effective in identifying the opportunities of improvement of the Product Development Process and in proposing Life Cycle Costs management practices.
Keywords: Gestão da qualidade; Ciclo de vida do produto; Gestão de custos do produto; Processo de desenvolvimento do produto; ENGENHARIAS::ENGENHARIA DE PRODUCAO